Towards a Unified Conceptual Framework of Translation - Cesar A. Hidalgo (Journal of Modern Languages)
The unified theory of translation is proposed in this study, bringing together philological theories and linguistic theories in translation. Each of these two theories enrich the other in the process, in a framework that views translation as a set of general rules commencing with meaning, moving on to manifestation and ending in responses in the rendering of a text from Lg1 to Lg2, i.e. T - MI + M2.